EARLY RECOVERY AND STABILISATION WITH INSTRUMENTATION IN ANTERIOR CERVICAL SPINE TUBERCULOSIS - Raja, Raja RA; Sheikh, Aleem -ud-Din; Hussain, Hussain M; Agani, Agani SA (Journal of Ayub Medical College Abbottabad, 2012)
Background: Tuberculous infection causes destruction, caseation, and necrosis of cervical vertebrae or may present as an abscess. Complete recovery of neurological status is the rule after anterior surgical decompression and fusion, even in cases with complete paraplegia or tetraplegia. Neurological impairment and spinal deformity are the major concerns with spinal tuberculosis. Absolute nonoperative treatment was offered in pre antibiotic era. Since last decade great advances in terms of operative options drastically changed the scenario in management of caries spine and indications for surgery have been extended for early resolution of disease, quicker rehabilitation and prevention of late complications. Methods: During the period from 2005 to 2012, 336 patients of spinal tuberculosis were admitted in Department of neurosurgery, Liaquat University Hospital, Jamshoro. Forty-four patients were considered for surgery. All 44 patients underwent decompression through anterior cervical approach followed by fusion with iliac bone graft and then stabilization with titanium locking plate. Results: There were 20 males and 24 females. Neck pain was the chief complaint and improved in all cases. Patients had varying grades of motor weakness in upper and lower limbs. All the patients had good neurological recovery after surgery. No postoperative surgical complication found in any patient. Conclusion: Anterior cervical decompression, fusion and instrumentation with titanium plate fixation in patients with tuberculous spondylitis gives excellent results without untoward effects. Keywords: cervical spondylitis, Koch's spine, anterior instrumentation, cervical plating